PERENCANAAN PUSAT KEBUDAYAAN DAN KESENIAN KALTIM DI TENGGARONG DENGAN PENEKANAN PADA AKUSTIK - Hatta Musthafa Adham Putra; Zakiah Hidayati; M. Sutan Djaya Bunayya (Indonesian Society of Applied Science, 2021)
Indonesia has a diverse ethnic and cultural diversity that continues to grow in the lives of Indonesians. Each tribe and region have characteristic of various arts and become the pride of the region. Tenggarong is one of the district in Kutai Kartanegara regency that has a variety of arts. Kutai Kartanegara regency does not yet have the means to develop adequate creativity for its citizens to channel art expression and activities. Through Kaltim Cultural and Art Center is a container and facilities created for the artists, people and government of Kutai Kartanegara Regency in developing the potential of art and culture. This design process is created through several stages, namely the study of literature, observation and analysis of data that has been obtained so as to obtain the results of a design concept in accordance with the objectives. The east Kaltim Cultural and Art Centerwas created with Accoustic design concept and artificial lighting so that art performer and art connoisseurs can comfortably enjoy performaces and exhibitions. Kaltim Cultural and Art Center in Kutai Kartanegara Regency is expected to become an object of education, tourism, and creations that can become a new icon in Kutai Kartanegara regency especially Tenggarong district.